Optimization of Paclobutrazol Dose for Foliar and Drenching Applications under Water Deficit Stress in Chickpea (Cicer arietinum L.) - Soumya, P. R.; Kumar, Pramod (International Journal of Bio-resource and Stress Management, 2017)
Chickpea (Cicer arietinum L.) is the fourth most important pulse crop rich in protein by virtue of N2 fixation. Water deficit is a major limitation in chickpea production. Paclobutrazol (PBZ), a potential triazole, has been reported to provide plant protection against abiotic stresses. Therefore, an experiment was conducted using kabuli chickpea variety Pusa 1108 (sensitive to water deficit) to identify its optimum dose for foliar and drenching application. Water deficit stress was imposed by withholding the water at vegetative stage. Just prior to water stress treatment, plants were treated exogenously with varying dose paclobutrazol for foliar (0, 30, 60, 90, 120 and 150 mg l-1) and drenching (0, 60, 120, 180, 240 and 300 mg l-1) applications. Maximum enhancement of relative water content (RWC), membrane stability index (MSI), photosynthetic rate (PN), chlorophylla (chla), chlorophyllb (chlb) and total chlorophyll during water deficit stress and after recovery were obtained with the foliar application of PBZ @ 60 mg l-1 while for PBZ drenching @ 120 mg l-1. On an average, in general based on curve fitting of under taken physiological responses of chickpea to PBZ, optimum dose of PBZ foliar application was estimated 67.5 mg l-1 while for PBZ drenching 127 mg l-1.